2010
DOI: 10.1038/ajg.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Increases Risk of Death Among Patients With Diabetes: A Community-Based Cohort Study

Abstract: Introduction-The significance of non-alcoholic fatty liver disease (NAFLD) among patients with diabetes is unknown. We sought to determine whether a diagnosis of NAFLD influenced mortality among a community-based cohort of patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
192
4
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(212 citation statements)
references
References 31 publications
11
192
4
5
Order By: Relevance
“…It will only be possible to estimate the size of this presumed bias when there are robust ways of identifying people with all levels of severity of liver disease and their risk of outcomes of interest at a population level. Our estimates of the strength of the association between NAFLD and mortality or CVD are consistent with those of other studies that included people with the whole spectrum of NAFLD and in which there are fewer concerns about ascertainment and misclassification bias (11,17,18). This suggests that the opposing effect of the different biases in the way we have identified the NAFLD and comparison groups are approximately balanced, but this hypothesis clearly requires testing when suitable data are available.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It will only be possible to estimate the size of this presumed bias when there are robust ways of identifying people with all levels of severity of liver disease and their risk of outcomes of interest at a population level. Our estimates of the strength of the association between NAFLD and mortality or CVD are consistent with those of other studies that included people with the whole spectrum of NAFLD and in which there are fewer concerns about ascertainment and misclassification bias (11,17,18). This suggests that the opposing effect of the different biases in the way we have identified the NAFLD and comparison groups are approximately balanced, but this hypothesis clearly requires testing when suitable data are available.…”
Section: Discussionsupporting
confidence: 77%
“…A US cohort study of 337 people with T2DM, of whom 116 were diagnosed with NAFLD based on imaging or liver biopsy, suggested NAFLD was associated with increased all-cause mortality [age, sex and duration of diabetes adjusted hazard ratio 2.2; 95% confidence interval (CI) 1.1-4.2), mean follow-up 10.5 years] (17). An Italian study of 2103 people with T2DM of whom 157 had NAFLD, showed that NAFLD was associated with increased risk of incident CVD over 6.5 years: hazard ratio (95% CI) 1.9 (1.2-2.6) adjusted for age, sex, smoking, diabetes duration, LDL-cholesterol, medication and metabolic syndrome (18).…”
mentioning
confidence: 99%
“…Highly variable rates of NAFLD prevalence in the general population have been reported, with results ranging from 14% to 40% (2-5). NAFLD has been associated with an increased risk of death from malignancy or cardiovascular disease (CVD) (6,7). When individuals present the features of metabolic syndrome, such as overweight/obesity, hypertension, insulin resistance (IR), and dyslipidemia, it is necessary to envisage the possibility of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…118 In agreement, a study of 337 T2DM patients reported that NAFLD carried a two-fold increased risk of all-cause mortality (malignancy, CVD and liver-related complications) during a mean 11-year follow-up. 119 Growing evidence suggests that NAFLD is associated not only with liver-related morbidity or mortality, but also with an increased risk of developing CVD, i.e., the most common cause of death in T2DM. 8,120,121 Emerging evidence also suggests that NAFLD is associated with increased risk of microvascular diabetic complications (i.e., chronic kidney disease and advanced diabetic retinopathy) in people with T2DM.…”
mentioning
confidence: 99%